2017
DOI: 10.1111/cas.13341
|View full text |Cite
|
Sign up to set email alerts
|

Gankyrin induces STAT3 activation in tumor microenvironment and sorafenib resistance in hepatocellular carcinoma

Abstract: Most hepatocellular carcinomas (HCC) develop as a result of chronic liver inflammation. We have shown that the oncoprotein gankyrin is critical for inflammation‐induced tumorigenesis in the colon. Although the in vitro function of gankyrin is well known, its role in vivo remains to be elucidated. We investigated the effect of gankyrin in the tumor microenvironment of mice with liver parenchymal cell‐specific gankyrin ablation (Alb‐Cre;gankyrin f/f) and gankyrin deletion both in liver parenchymal and non‐parenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…In experiments investigating the underlying mechanism, PRMT1 accelerated HCC through the STAT3 pathway at the mRNA and protein levels. We also found that upregulating PRMT1 can increase STAT3 phosphorylation and thereby activate the STAT3 pathway, which can potentiate the development of HCC [22][23][24][25][26][27]. Finally, cryptotanshinone, a STAT3 inhibitor, suppressed HCC growth and migration through inhibiting STAT3 phosphorylation, which was activated by PRMT1 overexpression.…”
Section: Discussionmentioning
confidence: 61%
“…In experiments investigating the underlying mechanism, PRMT1 accelerated HCC through the STAT3 pathway at the mRNA and protein levels. We also found that upregulating PRMT1 can increase STAT3 phosphorylation and thereby activate the STAT3 pathway, which can potentiate the development of HCC [22][23][24][25][26][27]. Finally, cryptotanshinone, a STAT3 inhibitor, suppressed HCC growth and migration through inhibiting STAT3 phosphorylation, which was activated by PRMT1 overexpression.…”
Section: Discussionmentioning
confidence: 61%
“…In conjunction with a recent report showing that knockout of gankyrin suppressed HCC growth, 5 this study provided further insight into a potential molecular target for treating HCC by modulating tumor cell growth and proliferation. In addition, findings correlating gankyrin overexpression with poorer survival and advanced cancer stage render it an appealing and potentially novel prognostic tumor biomarker 6 .…”
supporting
confidence: 57%
“…In the course of these studies, we found that cyclin D3–cdk4 phosphorylates C/EBPα at Ser193 and increases formation of C/EBPα‐p300 complexes, which in turn activate enzymes of TG synthesis and cause hepatic steatosis . In addition to cdk4, several recent papers provide evidence that a number of strong initiators of liver proliferation and oncogenes are elevated in human liver biopsies from patients with NAFLD and in animal models of NAFLD at early stages of the disease . Previous studies suggested that hepatic steatosis causes further steps of NAFLD.…”
Section: Discussionmentioning
confidence: 92%
“…In agreement, it has recently been shown that some strong initiators of liver proliferation and oncogenes are elevated in human liver biopsies from patients and in animal models with NAFLD. These proliferative markers include the elevation of gankyrin (Gank), cyclin‐dependent kinase 4 (cdk4), and cyclin D3 and activation of the E2F1 pathway . Several recent reports showed that inhibition of cdk4 prevented and reversed the NAFLD phenotype .…”
mentioning
confidence: 99%
See 1 more Smart Citation